UNESCO'S ROLE REGARDING THE PROTECTION OF CULTURAL OBJECTS RECEIVING SPECIAL PROTECTION - Harahap, Muhammad Anwar Natama; Harisman, Harisman (Universitas Muhammadiyah Ponorogo, 2024)
The purpose of this writing is to determine UNESCO's role in protecting cultural objects that receive special protection by formulating a problem, namely: what is UNESCO's role in protecting cultural objects that receive special protection? The type of research used in this research is normative juridical. The data source used in this research uses secondary data. Qualitative analysis was carried out with an empirical starting point. The results of this research show that there are still limitations in safeguarding and regulating cultural heritage. Cultural heritage preservation is very important. This is intended to protect the historical, cultural and knowledge values contained therein. Illegal acts cannot actually be tolerated, because they can threaten the existence of cultural heritage. Therefore, the author believes that currently the world really needs security assistance and clear regulations to maintain the existence of cultural heritage. Of course, this can be realized if the 2003 UNESCO Convention is ratified.